Specifics of triathlon competitions - Leite, G.; Angelocci, L.; Borin, J. P. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The performance in Triathlon, sport that combines swimming, cycling and running has been much studied in recent years. Among them the studies of physiological responses of the triathlete and biomechanical analysis of methods that make up the Triathlon. However, there are few studies that address the specifics in these competitions. This study aimed is determine whether there are differences in the contribution of swimming, cycling and running performance in the overall results of Triathlon with different distances. It examined the performance of elite male athletes, top ten in race, in competitions of Triathlon held in Brazil in the last three years. For the characterization of evidence with different distances, the performance in swimming, cycling and running was correlated with the overall time of the different races analyzed, considering the significant correlations with p < 0.05. In step of Ironman held in Brazil, the modalities cycling and running were determinants (r = 0.88 and 0.77, p < 0.05, respectively), with swimming having no significance for the outcome (r = 0.35, p > 0.05). Brazilian Championship of Long Distance (3 km of swimming, 80 km cycling and 20 km running) running and cycling were the decisive manner (r = 0.93 and 0.85, p < 0.05, respectively), with swimming having no significance for the outcome (r = 0.50, p > 0.05). In the Brazilian Championship Olympic Triathlon (vacuum permitted), running and swimming were determinants (r = 0.99 and 0.74, p < 0.05, respectively) and cycling had negative influence on the performance of the race (r = - 0.79, p < 0.05). In Short Triathlon (vacuum permitted and allowed distances of 0.75 km of swimming, 20km cycling and 5km running), all procedures were important to the overall performance, especially the running (r = 0.90, p < 0.05), cycling (r = 0.85, p < 0.05) and finally the swimming (r = 0.66, p < 0.05). After the analysis and interpretation of data, we can conclude that: i) the tactics used in race with the vacuum permitted seems different the race without vacuum, ii) there are differences between the tactics employed for the Triathlon held at different distances, so it is necessary to analyze the distance from race to the athlete direct his tactics for the competition; iii) the running is the main modality in determining results of Triathlon, in the most distances analyzed. There is still a need for further studies on the performance of triathletes at different distances, including female athletes.